Structural MRI volumetric analysis in patients with organic amnesia, 1: methods and comparative findings across diagnostic groups. - Colchester, A; Kingsley, D; Lasserson, D; Kendall, B; Bello, F; Rush, C; Stevens, T; Goodman, G; Heilpern, G; Stanhope, N; Kopelman, MD (2001)
BACKGROUND: If they are to be replicable, MRI volume measurements require explicit definitions of structures and of criteria for delineating these structures on MRI. Previously published volumes in healthy subjects show considerable differences in measurements across different studies, including a fourfold variation in estimates of hippocampal volume. Previous neuroimaging reports in patients with Korsakoff syndrome have generally found widespread or non-specific change, whereas in patients with herpes encephalitis the extent of pathological involvement reported beyond the temporal lobes has varied. METHOD: In the present study, a clear set of anatomical criteria and detailed MRI segmentation procedures were applied to measure whole brain, frontal and temporal lobe, and anterolateral and medial temporal volumes, as well as thalamic areas in patients with organic amnesia (from Korsakoff's syndrome, herpes encephalitis, and focal frontal lesions) as well as healthy controls. RESULTS: Patients with Korsakoff's syndrome showed decreased thalamic measurements but no significant changes in the medial temporal lobes, whereas patients with herpes encephalitis showed severe medial temporal but not thalamic atrophy. In the patients with known frontal lobe lesions, quantitative analysis on MRI showed reduced frontal lobe volume but no significant temporal lobe or thalamic atrophy. CONCLUSION: Quantified MRI can be a useful technique with which to examine brain-cognitive relations, provided that detailed techniques are explicitly described. In particular, specific patterns of volume change can be found in vivo in patients with Korsakoff's syndrome and those with herpes encephalitis.